Modeling and simulating of stainless steel joints by the Friction stir welding - Silva, Yuri Cruz da (2021)
Friction Stir Welding (FSW) is a solid-state welding method developed 1991 at The Welding Institute (TWI). This method joins materials through plastic deformation caused by a rotational tool that moves between the materials interface. The scientific community has extensively studied this technique because its unique characteristics allow excellent results compared with conventional fusion welding processes. The low temperatures and high deformation rates during the process favor the existence of the dynamic recrystallization of the grains, improving the welded region mechanical properties. Numerical simulations were performed to understand the phenomena that involve the FSW joining of the AISI 304L and the AISI 410S steels. For this, this thesis was divided into four chapters. The Chapter 5 addressed the viscosity models used in this study and developed a methodology to determine the maximum viscosity to be defined in the simulation. Following the thesis, which comprises three more chapters, the next two have addressed the FSW process simulation applied for two different stainless steels: AISI 304L and AISI 410S. Theses steels ware chosen for their applicability in the industry. The materials were simulated as non-Newtonian fluids, where their viscosity depends on the process temperature and the strain rate. In the Chapter 6, a simulation was made for the similar welding of AISI 304L austenitic stainless steel, making it possible to calculate the extent of the welding zones. A parameter Y was also developed, depending on the minimum viscosity, applied pressure, and rotation. This parameter assists in the choice of conditions with less possibility of burr formation. Particles were injected into the model in order to trace its path along with the plate, and from that, we predict regions where defects of the wormhole type would be formed. Chapter 7 focus was on using the simulated temperature, which presented results very close to the experimental ones and associating it with thermodynamic simulations. In this study, it was possible to predict the formation of martensite and chromium carbides (Cr23C6) in different regions of the weld. The parameter Y was applied to this material, and its effectiveness was observed in all experimental tests, predicting the conditions with more burrs. In the Chapter 8, the Volume of Fluid (VOF) method was applied to the FSW simulation model already used to simulate the mixture of these materials in dissimilar welding and made it possible to observe the materials flow during the welding, and which side each material should be employed to obtain the best results. In this chapter, the simulation with a more realistic model of the tool was also developed, enabling the development of future works in the area.